PENGEMBANGAN MATERI AJAR TEKS DESKRIPSI BERMUATAN KEARIFAN LOKAL BATAK TOBA BERBANTUAN MEDIA WEB GOOGLE SITES UNTUK SISWA KELAS VII SMP SWASTA GAJAH MADA MEDAN - Maysarah; Atika Wasilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to, (1) describe the process of developing teaching materials for descriptive texts containing local wisdom using the Google Sites web, (2) describe the form of developing teaching materials for descriptive texts containing local wisdom of the Toba Batak using the Google Sites web, and (3) describe the feasibility of teaching materials for descriptive texts containing local wisdom of the Toba Batak using the Google Sites web. The development of teaching materials for descriptive texts containing local wisdom of the Toba Batak using the Google Sites web media uses the ADDIE model which is limited to only the analysis, design, and development stages. The validation stage involves lecturers who are material experts and lecturers who are media experts to assess the feasibility of the material and the feasibility of the media. The sample of this study was 28 students of class VII of Gajah Mada Private Middle School, Medan. Data collection techniques were by interviews and questionnaires. The research instrument was in the form of a validation questionnaire sheet for material experts and media experts using a Likert scale. Data analysis used quantitative descriptive analysis. The results of the study showed that the product of the descriptive text teaching material containing local wisdom of the Toba Batak with the help of the Google Sites web obtained the criteria of "Very Good" with an average of 94.96%, with the results from material experts of 90.90% with the criteria of "Very Good" and the results from media experts of 96% with the criteria of "Very Good" and subject teachers of 98% with the criteria of "Very Good" so that the teaching material is suitable for use as supporting teaching material in the learning process.